2007
DOI: 10.5123/s0101-59072007000400008
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de gardnerella e mobiluncus em exames de colpocitologia em Tome-Açu, Pará: Prevalence of gardnerella and mobiluncus in vaginal cytology examinations in Tome-Açu - Pará

Abstract: RESUMOObjetivo: a Gardnerella vaginalis,, isoladamente ou associada ao Mobiluncus sp., é um dos principais agentes causadores de infecções em mulheres em idade reprodutiva, seja pela falta de hábitos de higiene adequados, número de parceiros sexuais ou desequilíbrios da microflora vaginal. Assim, buscou-se verificar a prevalência de G. vaginalis e/ou Mobiluncus sp., associadas às condições sócio-culturais em mulheres atendidas no Hospital de Quatro Bocas de Tomé-Açu -Pará, através de exame preventivo de câncer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Concomitant infection between TV and G. vaginalis and TV and C. albicans were found in 3 women, respectively. The concomitant infection is commonly found in cases where TV makes the vaginal environment susceptible to infection by C. albicans, and other microorganisms, such as G. vaginalis joins leading to the development of bacterial vaginosis (BV) [24][25][26][27][28][29][30]. The presence of atypical squamous cells of unknown significance was observed in 10 of the sample population, and HPV characteristic lesions were observed in 14 women, and among them, 5/24 of women who show lesion on the pap smear, were infected concomitantly with TV.…”
Section: Discussionmentioning
confidence: 99%
“…Concomitant infection between TV and G. vaginalis and TV and C. albicans were found in 3 women, respectively. The concomitant infection is commonly found in cases where TV makes the vaginal environment susceptible to infection by C. albicans, and other microorganisms, such as G. vaginalis joins leading to the development of bacterial vaginosis (BV) [24][25][26][27][28][29][30]. The presence of atypical squamous cells of unknown significance was observed in 10 of the sample population, and HPV characteristic lesions were observed in 14 women, and among them, 5/24 of women who show lesion on the pap smear, were infected concomitantly with TV.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the age group, the mean age of patients with G. vaginalis verified in the present study was 42.34 years and a higher prevalence was observed in patients aged 51 to 60 years. Other studies carried out in Brazil reported higher prevalences of the microorganism in younger women, aged between 21 and 39 years (OLIVEIRA et al, 2007;BRINGEL et al, 2012;BARBOSA et al, 2021). Only one study, carried out in Maringá, PR, reported a higher prevalence of G. vaginalis in women older than 40 years, in which the mean age of the patients was 40.91 years (TONINATO et al, 2016).…”
mentioning
confidence: 95%